Moderasi Beragama: Analisis Bibliometrik pada Database Dimensions - Arifah Nur Istiqomah; Busro Busro (UIN Sunan Gunung Djati Bandung, 2023)
In this study, researchers will analyze articles with the keyword Religious Moderation based on research categories based on the objectives of the research field and goals for sustainable development, Trends/developments per year, Researchers/ Authors, and Place of publication/Journal Name. This is a quantitative method, where a literature study based on selected keywords of Religious Moderation is used to analyze past articles by collecting objective data or information for research. Research for this article the author conducted a bibliometric analysis on Dimensions with the year of publication being limited to 2003-2022. This bibliometric analysis was carried out with the help of the app.dimensions.ai database site in finding the various data needed. One of the reasons the author uses the Dimensions site is the site's ability to accommodate thousands of articles on the required themes. This research seeks to find data so that research can be more in-depth, so this research aims to be able to find out about the cultural diversity of the Indonesian nation, religious moderation in diversity and the role of religious instructors in realizing the peace of the Indonesian people. To realize the objectives of this study, the authors formulate a research problem with bibliometric dimensions data analysis.